Operational evaluation of a selected water supply network - Iwanek, Małgorzata; Suchorab , Paweł (Instal, 2019)
Analysis of water distribution network failure and water losses should be a basis for water supply companies to undertake activities related to network modernization. Water losses analysis should be conducted for District Meter Areas (DMAs) by comparing inflows and outflows from the area with billed water. In the paper the water network operating conditions were assessed basing on the case study and taking both failure rate and water losses into consideration. The analysis was conducted for the whole network, even though the network operates as divided into 2 zones. Based on the obtained results, it can be claimed that disregard of existing zones could cause the misinterpretation of the network operating conditions and hence impede the proper planning the network modernization and renovation.
Keywords: failure rate; water losses indicators; water balance